2015
DOI: 10.1002/2014jd022938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water clarity on lake stratification and lake‐atmosphere heat exchange

Abstract: Recent progress of including lake subroutines in numerical weather prediction (NWP) models has led to more accurate forecasts. In lake models, one essential parameter is water clarity, parameterized via the light extinction coefficient, K d , for which a global constant value is usually used. We used direct eddy covariance fluxes and basic meteorological measurements coupled with lake water temperature and clarity measurements from a boreal lake to estimate the performance of two lake models, LAKE and FLake. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
100
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 58 publications
12
100
0
1
Order By: Relevance
“…SDD is a suitable characteristic to describe water transparency for small values of K d . For high values of K d (ranging above 4 m −1 ), Arst et al (2008) and Heiskanen et al (2015) suggested that SDD is unable to describe any changes in K d . Figure 3 also shows that SDD cannot describe the scatter of K d for values above 4 m −1 .…”
Section: Evaluation Of Coastcolour K Dmentioning
confidence: 99%
See 3 more Smart Citations
“…SDD is a suitable characteristic to describe water transparency for small values of K d . For high values of K d (ranging above 4 m −1 ), Arst et al (2008) and Heiskanen et al (2015) suggested that SDD is unable to describe any changes in K d . Figure 3 also shows that SDD cannot describe the scatter of K d for values above 4 m −1 .…”
Section: Evaluation Of Coastcolour K Dmentioning
confidence: 99%
“…The study found a critical threshold for K d (0.5 m −1 ) in 1-D lake models. Heiskanen et al (2015) concluded that for too-clear waters (K d < 0.5 m −1 ), the model is much more sensitive to K d . The study recommends a global mapping of K d to run the FLake model for regions with clear waters (K d < 0.5 m −1 ) for future use in NWP models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, milder winters, shortening ice cover and less snow cover on ice occurring in NENA and around the northern latitudes [50,51] will all contribute to lowered lake albedo, earlier stratification and longer duration of energy absorption, resulting in intensified summer warming [11,12,52]. Changes in wind speed [53,54], water transparency [55,56] and hydrologic inflows [54] can all alter lake warming rates.…”
Section: Near-surface Warmingmentioning
confidence: 99%